Learning style preferences among Muslims pre-clinical medical students in an Islamic institution - Jamani, Nurjasmine Aida; Abd. Aziz, Karimah Hanim; Che Ab. Karim, Hanim Syazara; Nizar, Fatimah Azzahra; Dzulkarnain, Husna Najiah; Azimi, Muhammad Irham (2016)
Background: Educational experts affirm that students like various type of learning preference. It is known that the learning style preferences varies among medical students worldwide. By knowing types of learning style preferences, this will help medical educators to improve their way of conveying lectures and teaching in a more effective learning environment. Objectives:This study aimed to describe the pre-clinical medical students’ learning style preferences and its association with socio-demographic profile. Methods: This was a cross sectional study done among Year 1 and Year 2 Muslim pre- clinical year medical students in an Islamic institution in Kuantan Pahang. Medical students who fulfilled the inclusion and exclusion criteria were recruited using systematic random sampling. A validated learning style questionnaire (VARK) was used to assess their learning style. Descriptive statistics and bivariable analysis were used during analysis using SPSS version 23. Results: A total of 166 Muslim pre-clinical year medical students participated in this study. The mean (SD) age was 21.3(0.84). Majority of them were Malay (98.2%) and female (69.9%). Most of the students preferred unimodal learning style (80.1%) with the most preferred learning style preferences waskinesthetic (41.6%). Bivariable analysis showed female students preferred kinesthetic learning style compared to male students(p=0.02). Conclusion: In this study, majority of the pre-clinical year medical students preferred ‘life-like’ learning experience in their study. Hence, we recommend that medical educators to be more aware of the varieties of learning style preferences in order to improve the quality of teaching and learning experiences.